Investigating the effects of altered Rad51 expression on the DSB repair pathway choice and the conservation of RecA homologs in Saccharomyces cerevisiae - Rodrigo, Mahari (2023)
S. cerevisiae has been used as model Eukaryotic system because many of its genes are homologous to those in higher Eukaryotes and due to it’s ease of culturing. As a result, many reporter strains have been developed to investigate a range of cellular processes but, to generate deletion mutants in reporter strains, individual genes must be amplified from their respective strains in the Yeast Deletion Collection (YDO) and transformed individually into reporter strains. However, the bacterial Cas9 system may provide an alternative. Cas9 is an endonuclease which catalyses the formation of double strand breaks (DSBs), at specific loci. DSBs can be repaired by two major pathways, Non-Homologous End Joining (NHEJ), which is considered to be error prone or Homologous Recombination (HR), which is relatively error free. By targeting Cas9 to the desired genes, mutations can be created, provided the DSBs induced by Cas9 are repaired by NHEJ. In order to alter the DSB repair pathway choice, and force the cell to repair DSBs by NHEJ, the expression of Rad51, a recombinase involved in HR, was altered. Rad51 was placed under the control of a capped degron, a meiosis only promoter, PDMC1 and a mitosis only promoter, PCLB2. The sporulation efficiency and growth of the strains was assayed to determine whether they were comparable to wildtype, and therefore, could be used alongside reporter strains. While the strains generated may not be suitable, selection of a different target, such as proteins involved in resection or different promoters may yield the desired results. Cas9 may also have uses in identifying and sequencing novel recombinants, previous work in the Gray lab has identified ectopic recombinants whose partner locus is unknown. By adapting the sequencing tool Fusion Detection from Gene Enrichment (FUDGE) to detect novel recombinants forming from the HIS4::LEU2 and leu2::hisG hotspots, at abundances below the threshold of detection by pulsed-field gel electrophoresis. In addition, in order to investigate the conservation of protein binding domains across the Rec A homologs, Rad51 was replaced by several RecA homologs from across the Tree of Life. These strains were then driven through meiosis to determine whether the RecA homologs could compensate for Rad51. Interestingly, RadA, from Haloferax volcanii showed a partial compensation phenotype, when the sporulation efficiency was assayed, however no viable spores were generated.